Вывучэнне пахавальных помнікаў Беларускага Падзвіння XIV–XVIII стст. у дарэвалюцыйны перыяд - Чараўко, В. У. (Інстытут гісторыі НАН Беларусі, Мінск: Беларуская навука, 2010)
V. Charauko. Studying of the cemeteries of the Belarusian Dvina region in the 14th — 18th centuries till 1917 The first information about operations, that can be defined as amateur excavations of the memorials of Belarus-sian Dvina region, dates from the end of the 18th century. The archaeological studies of the late-medieval barrows and stone graves («zhamiks») took place in the 19th century. Those funeral monuments were researched by Z. Dalenha-Khadakhouski, M. Kustsinski, A. Semyantouski, E. Ramanau. F. Pakrouski published archaeological maps of Vilnya and Koven regions, where some old graveyards were reflected. However, the funeral monuments of the 14th — 18th centuries didn't become subject of special research in the pre-revolutionary period. Their exposure and research had random character, that fact doesn't belittle the importance of that discoveries. Першыя звесткі аб дзеяннях, якія могуць быць кваліфікаваны як аматарскія раскопкі пахавальных помнікаў Беларускага Падзвіння, адносяцца да канца XVIII ст. Археалагічнае вывучэнне познесярэднявечных курганоў і жальнікаў праводзілася ў ХІХ ст. Гэтыя пахавальныя помнікі даследаваліся З. Даленга-Хадакоўскім, М.Ф. Кусцінскім, А.М. Семянтоўскім, Я.Р. Раманавым. Ф.В. Пакроўскі апублікаваў археалагічныя карты Віленскай і Ковенскай гурберняў, дзе былі адлюстраваны некаторыя старыя могілкі. Первые сведения о действиях, которые могут быть квалифицированы как любительские раскопки погребальных памятников Белорусского Подвинья, относятся к концу XVIII века. Археологическое изучение позднесредневековых курганов и жальников проводилось в ХIХ в. Данные погребальные памятники исследовались З. Доленго-Ходаковским, М.Ф. Кусцинским, А.М. Сементовским, Е.Р. Романовым. Ф.В. Покровский опубликовал археологические карты Виленской и Ковенской губерний, где были отражены некоторые старые кладбища.